Convergent validity of the preliminary Spanish version of the Child Abuse Potential Inventory: depression and marital adjustment - Arruabarrena, M I; de Paúl, J (Child abuse & neglect, 1992)
This paper studies the "convergent validity" of the preliminary spanish version of the Child Abuse Potential (CAP) Inventory. In relation to the ecological-systemic model of child maltreatment, this inventory evaluates individual, family, and social factors which facilitate the occurrence of physical child abuse. Depression and marital adjustment were measured in three groups of mothers: one group of mother-perpetrators of physical child abuse (n = 20), another group of mothers with a rate superior to cut-off (percentile = 95) in the CAP Inventory (n = 15), and a group of mothers with low punctuation (under percentile 25) in the CAP Inventory (n = 15). The two last groups (High CAP and Low CAP) come from a larger sample of 829 subjects which are a demographically representative sample of the population of País Vasco (in Spain). Because of variations in the detection of social services, the physically abused group is formed by the most extreme and severe cases. The three groups of mothers were matched as to socio-economic family status, education, civil status, age of the mother, sex of the child, number of children. It was expected that in these variables, depression and marital adjustment, the group with physical abuse would resemble the High CAP group and that both groups would be significantly different from the Low CAP group. Results partially confirm these hypothesis, supporting the possibilities of developing a Spanish version of the CAP Inventory for detection of physical child abuse.